Management of Intra-Abdominal Infection Patients with Septic Shock in the ICU - Ariaty, Geeta Maharani; Rismawan, Budiana (CoinReads Media Prima, 2025)
Introduction: Intra-abdominal infections (IAIs) complicated by septic shock pose a critical challenge in intensive care units (ICUs) due to high morbidity and mortality. Effective management requires rapid diagnosis, source control, and optimized antimicrobial therapy. This case report describes the multidisciplinary approach to managing IAI with septic shock, highlighting evidence-based strategies. Case Description: A 59-year-old male presented with septic shock secondary to generalized peritonitis caused by an incarcerated hernia. Initial management included fluid resuscitation with 1,500 mL Ringer’s lactate, norepinephrine, and broad-spectrum antibiotics (meropenem and metronidazole). Emergency laparotomy within 4.5 hours achieved source control by evacuating 300 mL of purulent peritoneal fluid. ICU care involved mechanical ventilation, analgesia (fentanyl, paracetamol), sedation (midazolam, transitioned to dexmedetomidine), and enteral nutrition starting on day three. Multidisciplinary collaboration facilitated hemodynamic stabilization, extubation on day five, and transfer to the high-care unit on day six, with significant clinical improvement. Conclusion: Successful management of IAI with septic shock hinges on timely source control, appropriate antimicrobial therapy, and comprehensive ICU care. The absence of microbiological cultures, a key limitation, underscores the need for improved diagnostic access in resource-limited settings. Adherence to evidence-based protocols and multidisciplinary expertise are critical to improving survival. Future efforts should focus on enhancing diagnostics to optimize therapy and reduce antimicrobial resistance.